Controlled porosity alumina structures for ultra-precision hydrostatic journal bearings - Durazo-Cardenas, Isidro; Stephenson, David J.; Corbett, John (Blackwell Publishing Ltd., 2010)
A series of fine-grade alumina powders has been used in combination with maize starch granules to produce porous structures for porous hydrostatic journal- bearing applications. A comprehensive series of tests was conducted to characterize porosity in terms of density, pore size, and permeability. Successful processing of quality journal-bearing components has been demonstrated for preferred combinations of alumina size and starch content, using fixed-processing parameters. The new porous ceramic bearings showed consistent and reproducible properties and are suitable for a wide range of higher precision engineering applications. The porous ceramic-bearing processing route has also proved to be low cost and environmentally sound.